Thermodynamic analysis of high-temperature pumped thermal energy storage systems: Refrigerant selection, performance and limitations - Abdelrahman H. Hassan; Laura O’Donoghue; Violeta Sánchez-Canales; José M. Corberán; Jorge Payá; Henning Jockenhöfer (Energy Reports, 2020)
One of the bottlenecks for a wider implementation of renewable energies is the development of efficient energy storage systems which can compensate for the intermittency of renewable energy sources. Pumped thermal energy storage (PTES) is a very recent technology that can be a promising site-independent alternative to pumped hydro energy storage or compressed air energy storage, without the corresponding geological and environmental restrictions. Accordingly, this paper presents a full thermodynamic analysis of a PTES system consisting of a high-temperature heat pump (HTHP), which drives an organic Rankine cycle (ORC) by means of an intermediate high-temperature thermal energy storage system (HT-TES). The latter combines both latent and sensible heat thermal energy storage sub-systems to maximize the advantage of the refrigerant subcooling. After validating the proposed model, several parametric studies have been carried out to assess the system performance using different refrigerants and configurations, under a wide range of source and sink temperatures. The results show that for a system that employs the same refrigerant in both the HTHP and ORC, and for a latent heat thermal energy storage system at 133ºC, R-1233zd(E) and R-1234ze(Z) present the best performance. Among all the cases studied with a latent heat thermal energy storage system at 133°C, the best system performance, also considering the impact on the environment, has been achieved employing R-1233zd(E) in the HTHP and Butene in the ORC. Such a system can theoretically reach a power ratio of 1.34 under HTHP source and ORC sink temperatures of 100 and 25°C, respectively.